SUSTAINABILITY REPORT INDUSTRI TEMBAKAU DI INDONESIA: PENERAPAN SASB STANDARDS DAN IMPLIKASINYA - Da Rato, Nicolaus Wahana (Ultimaccounting Jurnal Ilmu Akuntansi, 2024)
Abstract— This study analyzes the implementation of Sustainability Accounting Standards Board (SASB) standards in sustainability reports of the tobacco industry in Indonesia. The industry faces significant scrutiny regarding the health impacts of its products, with the World Health Organization (WHO) reporting 8 million annual deaths worldwide due to tobacco. Despite various regulatory measures aimed at reducing tobacco consumption and its associated risks, such as smoking-free areas and high taxes, tobacco production and consumption in Indonesia continue to rise. Findings indicate that the majority of tobacco companies, including PT Gudang Garam Tbk and PT Hanjaya Mandala Sampoerna Tbk, fall short of SASB standards, particularly in disclosing material health-related information. The reports also reveal potential instances of greenwashing, where companies promote environmental initiatives while neglecting the negative health impacts of their products. The research emphasizes the urgency for these companies to enhance their sustainability disclosures, ensuring accuracy and relevance in line with SASB standards. Improving transparency and accountability in sustainability reporting will foster public trust and support public health. Keywords: Sustainability Reporting; Tobacco Industry; SASB Standards; Greenwashing; Disclosure Practices